Behavioral Traits Associated With Resilience to the Effects of Repeated Social Defeat on Cocaine-Induced Conditioned Place Preference in Mice - Calpe-López, Claudia; García-Pardo, Maria Pilar; Martínez-Caballero, Maria Angeles; Santos-Ortíz, Alejandra; Aguilar, Maria Asunción (Frontiers in Behavioral Neuroscience, 2020)
The relationship between stress and drug use has been well demonstrated. Stress induced by repeated social defeat (RSD) induces an enhancement of the conditioned place preference (CPP) induced by cocaine in mice. Recently, interest in the phenomenon of resilience, understood as the ability of subjects to overcome the negative effects of stress, has increased. Our aim is the behavioral characterization of resilient animals regarding the effects of RSD on the CPP induced by cocaine. To this end, C57BL/6 male mice were exposed to stress by RSD during late adolescence (n= 25) while others did not undergo stress (controls, n= 15). On the following two days after the last defeat, all the animals carried out the Elevated Plus Maze (EPM), Hole Board, Social Interaction, Tail Suspension and Splash tests. At 3 weeks, all the animals performed the CPP with a low dose of cocaine (1 mg/kg). Exposure to RSD decreased all measurements related to the open arms in the EPM. It also reduced social interaction, decreased immobility in the tail suspension and reduced grooming in the splash test. RSD exposure also increased the sensitivity of mice to the rewarding effects of cocaine, since only defeated animals acquired CPP. Several behavioral traits were related to resilience to the potentiating effect of RSD on cocaine CPP. Mice that showed less submission during defeat episodes, less percentage of time in the open arms of the EPM, low novelty seeking, high social interaction, more immobility in the tail suspension test and a higher frequency of grooming were the mice resilient to the long-term effects of social defeat on cocaine reward, since they behaved like the controls and did not develop CPP. These results suggest that the behavioral profile of resilient defeated mice is characterized by an active coping response during episodes of defeat, a greater concern for the potential dangers, less reactivity in a situation of inevitable moderate stress and less depressive-like symptoms after stress. Determining the neurobehavioral substrates of resilience is the first step to develop behavioral or pharmacological interventions that increase resilience in individuals at high risk of suffering from stress.